Validation of novel low-dose CT methods for quantifying bone marrow in the appendicular skeleton of patients with multiple myeloma: initial results from the [¹⁸F]FDG PET/CT sub-study of the Phase 3 GMMG-HD7 Trial - Sachpekidis, Christos; Hajiyianni, Marina; Grözinger, Martin; Piller, Maja; Kopp-Schneider, Annette; Mai, Elias K.; John, Lukas; Sauer, Sandra; Weinhold, Niels; Menis, Ekaterina; Enqvist, Olof; Raab, Marc-Steffen; et al. (European journal of nuclear medicine and molecular imaging, 2025)
The clinical significance of medullary abnormalities in the appendicular skeleton detected by computed tomography (CT) in patients with multiple myeloma (MM) remains incompletely elucidated. This study aims to validate novel low-dose CT-based methods for quantifying myeloma bone marrow (BM) volume in the appendicular skeleton of MM patients undergoing [18F]FDG PET/CT.